Photocurable resin composition, hard coat film for molding, and molded article based thereon
The photocurable resin composition, combining urethane acrylate and alumina fine particles, addresses moldability and scratch resistance issues in hard coat films, ensuring durability and flexibility for automotive uses.
Patent Information
- Application Number
- JP2023096973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2043-06-13
AI Technical Summary
Existing hard coat films for automotive applications face challenges in achieving high elongation at break, good moldability, and scratch resistance, particularly in withstanding car washes, while maintaining durability and flexibility.
A photocurable resin composition comprising urethane acrylate derived from pentaerythritol triacrylate and isophorone diisocyanate, combined with alumina fine particles, a leveling agent, and a photopolymerization initiator, along with optional light stabilizers, to enhance scratch resistance and moldability.
The composition achieves high elongation at break, excellent moldability, and superior scratch resistance, including resistance to car washes, making it suitable for automotive exterior applications.
Smart Images

Figure 2024178663000001 
Figure 2024178663000002 
Figure 2024178663000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a photocurable resin composition having excellent moldability, a molding hard coat film having a cured resin layer thereof, and further to a molded article using the same. [Background technology]
[0002] Acrylic photocurable resins are used in many fields to impart special properties to the surfaces of plastic films and plastic molded products. For example, hard coat films, which are applied to PET (polyethylene terephthalate) films to impart high hardness, are used in large quantities as films for touch panels and molding films.
[0003] Among these, a molding film is well known for use in molding, in which a pattern is printed on the film surface, and then the film is softened by heating to perform three-dimensional molding. However, if the hard coat resin layer applied to the film is hardened, microcracks are likely to occur on the curved surface when the film is processed into a three-dimensional shape, and there are limitations on the shape that can be processed. For this reason, the applicant previously invented a hard coat agent containing a triazine ring-containing (meth)acrylate prepolymer and organic fine particles with an average primary particle size of 80 to 500 nm as a hard coat resin for insert molding that achieves both surface hardness and moldability (Patent Document 1). This hard coat agent has a film thickness of 1 to 10 μm and is excellent in that it can achieve both sufficient flexibility and surface physical properties.
[0004] By selecting a hard coat agent suitable for such molding applications, restrictions on processing have been alleviated to some extent, but as the applications of insert molding products expand, various properties are now required in addition to the moldability and abrasion resistance that have been required in the past. For example, in automotive exterior applications, in addition to stable moldability in large sizes, resistance to scratches caused by car washes is required, and there was no molding film with a hard coat layer that could meet these requirements. Therefore, there was a demand for a molding hard coat film that has the moldability, car wash scratch resistance, and durability that can be used for automotive exterior applications. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4848200 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a photocurable resin composition suitable for molding applications, which has high breaking elongation and good moldability, as well as scratch resistance sufficient to withstand washing in a car wash, a molding hard coat film coated with the same, and a molded product using the same. [Means for solving the problem]
[0007] In order to solve the above problems, the invention of claim 1 provides a photocurable resin composition comprising: urethane acrylate (A) obtained by further reacting pentaerythritol triacrylate with a diisocyanate obtained by reacting ethylene glycol with isophorone diisocyanate; alumina fine particles (B); a leveling agent (C); and a photopolymerization initiator (D); wherein the weight average molecular weight of (A) is 2,000 to 12,000.
[0008] The invention of claim 2 provides the photocurable resin composition according to claim 1, further comprising a light stabilizer (E).
[0009] The invention of claim 3 provides a molding hard coat film having a cured layer of the photocurable resin composition according to claim 1 or 2 on a plastic substrate.
[0010] The invention of claim 4 provides the hard coat film for molding according to claim 3, characterized in that the hard coat film for molding is used for exterior applications of vehicles.
[0011] The invention of claim 5 provides a method for producing an insert molded product, in which the molding hard coat film according to claim 3 is shaped using a mold, and then molten resin is injected from the side opposite to the photocurable resin cured layer to form a resin molded product.
[0012] The sixth aspect of the present invention provides an insert molded product or an out-molded product using the hard coat film for molding according to the third aspect of the present invention. Effect of the Invention
[0013] The photocurable resin composition of the present invention and the hard coat film (hereinafter referred to as HC film) coated with the same have high breaking elongation and good formability, as well as excellent scratch resistance, and are therefore useful as materials for molded products used in automotive exterior applications, such as roofs, bonnets, pillars, fenders, doors, headlamps, front grilles, bumpers, etc. BEST MODE FOR CARRYING OUT THEINVENTION
[0014] The photocurable resin composition of the present invention is composed of urethane acrylate (A) having a structure in which diisocyanate obtained by reacting ethylene glycol with isophorone diisocyanate (hereinafter referred to as IPDI) is further reacted with pentaerythritol triacrylate (hereinafter referred to as PETA), alumina fine particles (B), a leveling agent (C), and a photopolymerization initiator (D). In this specification, (meth)acrylate includes both acrylate and methacrylate.
[0015] The alicyclic diisocyanate IPDI used in the synthesis of (A) does not yellow and has excellent weather resistance stability, and at the same time has high rigidity, which can increase the hardness of the cured product. By reacting it with ethylene glycol, which has a very short carbon chain, it is possible to increase the concentration of urethane bonds in the molecule, forming a main skeleton with a linear structure that is highly rigid and has excellent chemical resistance. If polyethylene glycol is used instead of ethylene glycol, the concentration of urethane bonds tends to decrease, resulting in a decrease in chemical resistance.
[0016] The synthesis method of (A) is not particularly limited, and a known method can be used. The reaction may be performed without a solvent, but since stirring may become difficult as the molecular weight of (A) increases, ketones such as MEK, aromatic inactive solvents such as xylene, etc. may be used. In addition, it is preferable to use a catalyst for the reaction between the hydroxyl groups of ethylene glycol and PETA and the isocyanate groups. Examples of such a catalyst include tin-based catalysts such as dibutyltin dilaurate, and metal alkoxide-based catalysts such as cobalt naphthenate. The reaction temperature can be appropriately set, but is preferably 40 to 120°C, more preferably 60 to 100°C.
[0017] The weight average molecular weight (hereinafter referred to as Mw) of (A) is 2,000 to 12,000, preferably 3,000 to 11,000, and more preferably 3,500 to 10,000. If it is less than 2,000, the breaking elongation is low, so that it tends to be difficult to ensure sufficient moldability, and if it exceeds 12,000, the wear resistance and scratch resistance tend to decrease. The Mw of (A) can be adjusted by the molar ratio of ethylene glycol and IPDI to be reacted, and when the molar ratio of IPDI to ethylene glycol is close to each other, the Mw tends to be large. Note that the Mw was measured and calculated by gel permeation chromatography using a column using a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.
[0018] The blending amount of the (A) is preferably 70 to 95% by weight, more preferably 75 to 93% by weight, and particularly preferably 80 to 90% by weight, based on the total solid content. By making it 70% by weight or more, sufficient moldability and chemical resistance can be ensured, and by making it 95% by weight or less, sufficient scratch resistance and car wash scratch resistance can be ensured.
[0019] The alumina fine particles (B) used in the present invention are added for the purpose of increasing the hardness of the hardened layer to improve the abrasion resistance and improving resistance to scratches caused by car washes and the like. In general, the abrasion resistance is evaluated by using steel wool (hereinafter referred to as SW) with a load of about 200 to 500 g / 25 mmφ in a dry state to evaluate the degree of scratching. On the other hand, in an actual automatic car wash, a material with a relatively low elastic modulus (e.g., a polymeric rubber-based material) hits the coating surface with a strong force for a short time in a state where moisture is present. Since the way in which the force is applied to the coating surface is different in this way, even if the abrasion resistance by SW is good, scratches may occur in the car wash. The applicant has found through repeated trial and error that it is possible to improve the car wash scratch resistance by blending alumina fine particles, and further that it is possible to significantly improve the car wash scratch resistance by selecting alumina fine particles of a specific particle size.
[0020] The primary average particle size of (B) is preferably 10 to 200 nm, more preferably 40 to 150 nm, particularly preferably 50 to 130 nm, and particularly preferably 70 to 100 nm. By making it 10 nm or more, the car wash scratch resistance can be improved, and by making it 200 nm or less, good optical properties of the film can be secured. In particular, by making it 40 nm to 150 nm, the car wash scratch resistance is remarkably improved. The average particle size is the median diameter (d=50) measured by dynamic light scattering (DLS).
[0021] The amount of (B) is preferably 0.1 to 20.0% by weight, more preferably 0.5 to 15.0% by weight, particularly preferably 1.0 to 10.0% by weight, and particularly preferably 1.5 to 8.0% by weight, based on the total solid content of the resin composition. By making it 0.1% by weight or more, it is expected that the car wash scratch resistance can be improved, and by making it 20.0% by weight or less, sufficient moldability can be ensured.
[0022] The leveling agent (C) used in the present invention is blended for the purpose of improving the leveling properties during coating and improving the SW resistance of the cured film. It is preferable that the leveling agent has a reactive functional group capable of polymerizing with the binder resin to form a cured coating film, in order to prevent the cured film from being lost over time due to bleeding or the like and to maintain the weather resistance effect for a long period of time. For example, fluorine-based, silicone-based, fluorine silicone-based, etc. can be mentioned, and they can be used alone or in combination of two or more types.
[0023] Among these, silicone-based polysiloxane compounds that can equalize the large surface tension difference on the coating film surface are preferred. Examples include polyalkyl siloxanes, polyaryl siloxanes, polyalkylaryl siloxanes, polyester-modified siloxanes, polyether-modified siloxanes, etc., which can be used alone or in combination of two or more kinds.
[0024] The amount of (C) is preferably 0.1 to 3% by weight, more preferably 0.3 to 2% by weight, based on the total solid content. By adjusting the amount within this range, sufficient leveling properties can be ensured and a stable coating film appearance can be obtained. Commercially available products include BYK-UV3570 (product name: BYK Chemie, acryloyl group-containing polyester modified polydimethylsiloxane compound), etc.
[0025] The photopolymerization initiator (D) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, benzyl ketals include 2,2-dimethoxy-1,2-diphenylethan-1-one, α-hydroxyacetophenones include 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, α-aminoacetophenones include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, and acylphosphine oxides include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, which may be used alone or in combination of two or more.
[0026] Among these, it is preferable to use an α-hydroxyacetophenone type which is less prone to yellowing, and examples of commercially available products include Omnirad 127D, 184, and 2959 (product names: manufactured by IGM Resins Co., Ltd.) The amount of the (D) to be blended per 100 parts by weight of the radical polymerizable component is preferably 2 to 15 parts by weight, more preferably 5 to 12 parts by weight.
[0027] The photocurable resin composition of the present invention preferably further contains a light stabilizer (E). By incorporating (E), deterioration of the cured film caused by exposure to ultraviolet light or radiant heat when used outdoors can be reduced. For example, radical scavengers (e1) that efficiently trap alkyl radicals and peroxy radicals generated from polymers photodegraded by ultraviolet light, and ultraviolet absorbers (e2) that convert absorbed ultraviolet light energy into heat energy or the like to suppress decomposition of the polymer can be mentioned.
[0028] The (e1) may be, for example, a hindered amine type (hereinafter referred to as HALS type), a hindered phenol type, an aromatic amine type, etc., and may be used alone or in combination of two or more types. Among these, HALS type, which has high radical scavenging efficiency even at low concentration, is preferred. The blending amount of (e1) is preferably 1 to 10% by weight, more preferably 2 to 8% by weight, and particularly preferably 3 to 6% by weight, based on the total solid content. By setting it within this range, sufficient light stability can be ensured. Commercially available HALS-based products include Tinuvin 123 and Tinuvin 249 (trade name: manufactured by BASF Japan Ltd.), etc.
[0029] The (e2) is a radical chain initiation inhibitor having an absorption band in the harmful ultraviolet region with high energy, and by using it in combination with (e1), it is possible to further improve and stabilize weather resistance. For example, benzotriazole-based, triazine-based, benzophenone-based, etc. can be mentioned, and they can be used alone or in combination of two or more. Among these, hydroxyphenyltriazine-based, which can strongly absorb the long wavelength part of ultraviolet light, is preferable. The blending amount of (e2) is preferably 0.3 to 5 wt % based on the total solid content, more preferably 0.5 to 3.0 wt %, and particularly preferably 0.6 to 1.5 wt %. By setting it in this range, sufficient ultraviolet light absorption characteristics can be ensured. The blending amount of (E), which is the sum of (e1) and (e2), is preferably 1.0 to 12 wt % based on the total solid content, more preferably 1.5 to 10 wt %, and particularly preferably 4.0 to 8.0 wt %. By setting the content at 1.0% by weight or more, it is expected that the weather resistance will be improved, and by setting the content at 12% by weight or less, it is possible to avoid excessive blending and ensure sufficient adhesion to the substrate. Commercially available products include Tinuvin 460 and 477 (product names: manufactured by BASF Japan Ltd.).
[0030] To the photocurable resin composition of the present invention (hereinafter referred to as the present composition), reactive diluents, adhesion promoters, bluing agents, pigments, defoamers, thickeners, suspending agents, antistatic agents, antifogging agents, antibacterial agents, waxes, matting agents, hydrophilic agents, water repellents, inorganic fillers, organic fine particles, and the like may be added as necessary within the limits not impairing the performance.
[0031] As the reactive diluent, it is preferable to use a polyfunctional (meth)acrylate, because it has low viscosity and excellent compatibility with (A). For example, bifunctional diluents include (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, and dicyclopentanyl diacrylate; trifunctional dimethylolpropane tri(meth)acrylate and pentaerythritol tri(meth)acrylate; tetrafunctional ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, and diglycerin tetra(meth)acrylate; pentafunctional dipentaerythritol penta(meth)acrylate; and hexafunctional dipentaerythritol hexa(meth)acrylate. These diluents can be used alone or in combination of two or more.
[0032] The amount of the reactive diluent is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, based on 100 parts by weight of (A). By making it 20 parts by weight or less, it is possible to improve the reactivity while ensuring sufficient moldability. The blending ratio to the total solid content is preferably 15% by weight or less, more preferably 10% by weight or less.
[0033] When applying the composition to a plastic substrate, it may be diluted with a solvent to improve the coating properties. For example, alcohol-based solvents such as ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and diacetone alcohol, ketone-based solvents such as acetone, methyl ethyl ketone (hereinafter referred to as MEK), methyl isobutyl ketone, and cyclohexanone, ester-based solvents such as ethyl acetate and butyl acetate, ether-based solvents such as propylene glycol monomethyl ether (hereinafter referred to as PGM), diethyl ether, and diisopropyl ether, and hydrocarbon-based solvents such as cyclohexane and methylcyclohexane can be used alone or in combination of two or more kinds. The solid content when diluted is 10 to 70%, but there is no particular specification and it can be appropriately set to a viscosity that is easy to apply.
[0034] Examples of plastic substrates onto which the composition can be applied include polyester films, triacetyl cellulose films, polycarbonate films, polysulfone films, nylon films, cycloolefin films, acrylic (hereinafter referred to as PMMA) films, polyimide films, ABS films, polyolefin films, PVC films, and PVA films.
[0035] Among these, it is preferable to use a composite substrate made of a polycarbonate (hereinafter referred to as PC) substrate, which has excellent impact resistance and high heat resistance, and an acrylic substrate, which has high transparency and hardness. Here, the composite substrate made of a PC substrate and an acrylic substrate (hereinafter referred to as the present composite substrate) means a resin laminate having an acrylic resin layer on at least one side of a PC resin layer. The method for laminating the PC resin and the acrylic resin is preferably a co-extrusion molding method.
[0036] For the purpose of improving adhesion to the composition, the plastic substrate may be subjected to a surface treatment such as a primer treatment, a sandblasting method, a solvent treatment, or the like to create a rough surface, or a surface oxidation treatment such as a corona discharge treatment, a chromate treatment, or an ozone / ultraviolet light irradiation treatment.
[0037] The method for applying the composition is not particularly limited, and the composition can be formed by known coating methods such as spray coating, roll coating, die coating, air knife coating, blade coating, spin coating, reverse coating, gravure coating, wire bar, etc., or printing methods such as gravure printing, screen printing, offset printing, inkjet printing, etc. The coating thickness is, for example, 1 μm to 10 μm when dried, but is not limited thereto.
[0038] The light source of ultraviolet radiation used to cure the composition includes low pressure mercury lamps, high pressure mercury lamps, extra high pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, electrodeless ultraviolet lamps, etc., and the atmosphere for irradiation may be air or an inert gas such as nitrogen or argon. In addition, the curability can be further improved by heating the coating film during ultraviolet radiation using a back roll or an IR heater. Irradiation conditions include an irradiation intensity of 500 mW / cm. 2 ~3000mW / cm 2 , exposure dose 50-400mJ / cm 2 are given as examples, but are not limited to these.
[0039] The HC film (hereinafter referred to as the present HC film) obtained by coating the present composition on a plastic substrate and curing it preferably has a breaking elongation of 50% or more, more preferably 100% or more, and particularly preferably 200% or more in an atmosphere at 130° C. By making the breaking elongation 50% or more, sufficient moldability can be expected.
[0040] When using this HC film for the exterior of a car, the weather resistance is estimated at UVB (0.55 W / m 2 ) at 60°C for 1000 hours, ΔE is preferably 1.0 or less, more preferably 0.8 or less, and even more preferably 0.5 or less. By making it 1.0 or less, damage to the decorative layer caused by transmitted ultraviolet light can be reduced, and even if red or blue, which has poor UV resistance, is used in the decorative layer, discoloration over time can be kept low.
[0041] The HC film can be provided with a decorative layer as necessary. Methods for decoration include, for example, printing and metal deposition, and both may be used for decoration. Furthermore, an adhesive layer or a primer layer may be provided to improve adhesion with the injection molding resin.
[0042] A protective film may be attached to the HC film to protect the surface to which the composition is applied. By using a protective film, scratches during the insert molding or out-molding process can be prevented, and an improvement in yield can be expected.
[0043] The method of using the present HC film in insert molding can be, for example, to place the surface coated with the present composition facing the inner wall surface of the mold (so that the surface opposite the cured layer of the present composition is in contact with the molding resin), and if necessary, to preform the present HC film to conform to the shape of the mold, and then to close the mold and inject molten molding resin into the cavity and solidify the resin to form a resin molded product.
[0044] The preforming method may be a method in which the HC film is preheated to above its softening point and placed in a mold, and vacuum-suctioned through a suction hole in the mold, or a known molding method such as vacuum molding, compressed air molding, press molding, etc., using a molding mold other than the injection molding mold. It is also possible to perform molding and integral molding of the injected resin simultaneously by the injection pressure of the molding resin without performing these preforming methods.
[0045] The resin to be injection molded can be a known resin that can be injection molded. For example, polyethylene resin, polypropylene resin, polystyrene resin, ABS resin, AS resin, acrylic resin, urethane resin, polyester resin, polycarbonate resin, polyphenylene ether resin, polyacetal resin, polysulfone resin, etc. can be used alone or in combination of two or more. In the case of a large size such as an automobile body, or in the case of a small size but thin thickness, defects such as warping can be avoided by making the shrinkage rate after molding similar to that of an HC film.
[0046] In addition, by coloring the injection molding resin itself, it is possible to eliminate the decorative layer of the HC film or to fuse the color of the decorative layer with that of the injection molding resin, thereby creating a more profound appearance. Furthermore, in cases where products whose exteriors are colored with paint, such as automobile bodies, are replaced with insert molding, it is possible to omit the exterior painting with paint by coloring the injection molding resin. In this case, it is possible to eliminate appearance defects such as orange peel and pits that often occur with exterior painting.
[0047] Furthermore, this HC film can also be used for out-molding. For example, it can be used for TOM (Three-Dimensional Overlay Method) molding. TOM molding is a film molding method in which a substrate that has been preformed in an airtight box is subjected to three-dimensional surface decoration using vacuum and air pressure molding. By using this HC film, it is possible to handle large three-dimensional products regardless of the substrate material.
[0048] The present invention will be described in detail below with reference to examples and comparative examples, but these are illustrative and are not intended to be limiting. Unless otherwise specified, measurements were performed at room temperature of 25°C and relative humidity of 65%. The blend amounts are expressed as parts by weight in terms of solid content.
[0049] Preparation of ureac 1 In a four-neck flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200 parts by weight of ethylene glycol, 825 parts by weight of IPDI (NCO group 37.5%), a catalyst, and MEK were charged to a solid content of 50%, and the mixture was stirred and reacted at 80°C for 6 hours. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 438 parts by weight of PETA (hydroxyl value 120 mg KOH / g) was added and the mixture was stirred and reacted at 70°C for 6 hours. After confirming the disappearance of the isocyanate group by infrared absorption analysis, the solid content was adjusted to 50% with MEK to obtain 6-functional ureac 1 with Mw 6,200.
[0050] Preparation of ureac 2 In a four-neck flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200 parts by weight of ethylene glycol, 930 parts by weight of IPDI (NCO group 37.5%), a catalyst, and MEK were charged to a solid content of 50%, and the mixture was stirred and reacted at 80°C for 6 hours. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 886 parts by weight of PETA (hydroxyl value 120 mgKOH / g) was added and the mixture was stirred and reacted at 70°C for 6 hours. After confirming the disappearance of the isocyanate group by infrared absorption analysis, the solid content was adjusted to 50% with MEK to obtain 6-functional ureac 2 with Mw 3,200.
[0051] Preparation of ureac 3 In a four-neck flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200 parts by weight of ethylene glycol, 895 parts by weight of IPDI (NCO group 37.5%), a catalyst, and MEK were charged to a solid content of 50%, and the mixture was stirred and reacted at 80°C for 6 hours. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 743 parts by weight of PETA (hydroxyl value 120 mgKOH / g) was added and the mixture was stirred and reacted at 70°C for 6 hours. After confirming the disappearance of the isocyanate group by infrared absorption analysis, the solid content was adjusted to 50% with MEK to obtain 6-functional ureac 3 with Mw 3,800.
[0052] Preparation of ureac 4 In a four-neck flask equipped with a stirrer, reflux condenser, dropping funnel, and thermometer, 200 parts by weight of ethylene glycol, 790 parts by weight of IPDI (NCO group 37.5%), a catalyst, and MEK were charged to a solid content of 50%, and the mixture was stirred and reacted at 80°C for 6 hours. The reaction was terminated when the peak of the isocyanate group reached a specified amount by infrared absorption analysis. Next, 295 parts by weight of PETA (hydroxyl value 120 mgKOH / g) was added and the mixture was stirred and reacted at 70°C for 6 hours. After confirming the disappearance of the isocyanate group by infrared absorption analysis, the solid content was adjusted to 50% with MEK to obtain 6-functional ureac 4 with Mw 9,800.
[0053] According to the above-mentioned method, Ureacs A and B, which have the same skeleton as Ureacs 1 to 3 but different Mw, were obtained. UreaC A: PETA-IPDI-(ethylene glycol-IPDI) n -PETA backbone, 6 functions, solids content 50%, Mw 1,800 Urea B: PETA-IPDI-(ethylene glycol-IPDI) n -PETA backbone; 6 functional groups, solid content 50%, Mw 13,000
[0054] Examples 1 to 11 The above-prepared Ureacs 1 to 4 were mixed as (A), alumina microparticles having average particle sizes of 70 nm, 100 nm, 50 nm, and 25 nm were mixed as (B), BYK-UV3570 (trade name: manufactured by BYK Chemie, an acryloyl group-containing polyester-modified polydimethylsiloxane compound) was mixed as (C), Omnirad2959 and 127D (trade names: manufactured by IGM Resins) were mixed as (D), Tinuvin 249 (trade name: manufactured by BASF Japan) was mixed as (e1), and Tinuvin 477 (trade name: manufactured by BASF Japan) was mixed as (e2) in the proportions shown in Tables 1 and 2, and the mixture was stirred until uniformly dissolved and dispersed. PGM was then added so that the solid content was 30%, and the mixture was diluted and stirred to obtain photocurable resin compositions of Examples 1 to 11.
[0055] Comparative Examples 1 to 5 In addition to the materials used in the examples, the above-mentioned Ureacs A and B were used as oligomers, and PGM-AC-4130Y (product name: nanosilica, average particle size 40 to 50 nm, manufactured by Nissan Chemical Industries, Ltd.) was used as a filler in place of alumina fine particles. The mixture was stirred until uniformly dissolved and dispersed in the formulation shown in Table 3, and PGM was further added to the mixture so that the solid content was 30%, followed by dilution and stirring to obtain photocurable resin compositions for Comparative Examples 1 to 5.
[0056] Table 1 JPEG2024178663000001.jpg150145
[0057] Table 2 JPEG2024178663000002.jpg147161
[0058] Table 3 JPEG2024178663000003.jpg146141
[0059] The evaluation method was as follows.
[0060] Preparation of HC film 1 The photocurable resin compositions prepared in the examples and comparative examples were applied to the PMMA side of an Iupilon film (product name: DF02PUL, manufactured by Mitsubishi Gas Chemical Company, thickness 125 μm, PMMA / PC laminate film) so that the dry film thickness was 3 μm. The film was then dried in a thermostatic chamber at 80°C for 1 minute, and then exposed to a high-pressure mercury lamp with an output of 1300 mW / cm. 2 The film was irradiated with ultraviolet light so that the accumulated light amount was 200 mJ to prepare a film for evaluation.
[0061] Chemical resistance: Hand cream, Neutrogena SPF45 (product name: Johnson & Johnson) was applied to the cured film and left at 80°C for 24 hours, then returned to room temperature and wiped off, after which the surface was observed. No traces of application were marked with an O, and traces with an X.
[0062] Abrasion resistance: Using a friction tester FR-IBS manufactured by Suga Test Instruments, the resin composition coated surface of the hard coat film was rubbed back and forth 100 mm at a speed of 1 reciprocation per second with a load of 9 N applied to a friction element (diameter 16 mm) equipped with a test white cotton cloth (Kanakin No. 3). After 100 reciprocations, the presence or absence of scratches was checked, with an ◯ indicating no scratches and an × indicating scratches.
[0063] Adhesion: In accordance with the cross-cut method of JIS K 5600-5-6, a 10 x 10 grid was created with 1 mm intervals on the coated surface, and cellophane tape CT-24 (product name: manufactured by Nichiban Co., Ltd.) was attached and pulled upward to check the peeling condition, with a ◯ indicating no peeling and an × indicating peeling. No peeling: 100 / 100, Peeling: 0 / 100~99 / 100
[0064] Formability: The HC film was cut to 25mm wide x 110mm long, and a tensile test was performed using Minebea TechnoGraph TGI-1KN, with a chuck distance of 50mm, an atmospheric temperature of 130°C, and a tensile speed of 300mm / min. Cracks were visually confirmed, and the elongation rate was rated as × for less than 50%, △ for 50% to 100%, ◯ for over 100% to 200%, and ◎ for over 200%. Calculation formula: Calculate how many mm it has stretched based on 50 mm as the base. Stretched length (mm) / 50mm x 100 = stretch rate %
[0065] Abrasion resistance: Using a Toyo Seiki abrasion tester with a contact area of 4 cm 2 A 500g load was placed on the steel wool #0000 and the test was repeated 10 times at a reciprocating speed of 30 times per minute. The haze before and after the test was then measured using Haze-GARD2 manufactured by Toyo Seiki Seisakusho in accordance with JIS K7136. A haze increase of 5% or more was marked as x, and an increase of more than 5% was marked as o.
[0066] Car wash scratch resistance: A car wash abrasion resistance tester (manufactured by Amtec Kistler GmbH) was used to carry out the test in accordance with DIN EN ISO20566. The gloss of the coating film (measurement angle 20°) before and after the test was measured using micro-tri-gloss (manufactured by BYK), and the gloss retention was calculated using the following formula. A gloss retention rate of less than 50% was marked as ×, 50% to 75% was marked as ◯, and over 75% was marked as ◎. Gross retention rate (%) = Gross after test / Gross before test
[0067] Evaluation results of Examples 1 to 5 Table 4 JPEG2024178663000004.jpg88135
[0068] Evaluation results of Examples 6 to 10 Table 5 JPEG2024178663000005.jpg77135
[0069] Comparative Example Evaluation Results Table 6 JPEG2024178663000006.jpg88135
[0070] The examples were good without any problems in all respects, including chemical resistance, abrasion resistance, adhesion, moldability, scratch resistance, and car wash scratch resistance. In addition, it was confirmed that the inclusion of alumina fine particles (B) improved the car wash scratch resistance, and the effect was particularly remarkable when the average particle diameter was 50 to 100 nm.
[0071] On the other hand, Comparative Example 1, which does not contain (C), was inferior in abrasion resistance, scratch resistance, and car wash scratch resistance, and Comparative Example 2, which does not contain (B), was inferior in scratch resistance and car wash scratch resistance. Comparative Example 3, which used nanosilica with approximately the same particle size as the alumina fine particles, was inferior in abrasion resistance, scratch resistance, and car wash scratch resistance. Furthermore, Comparative Example 4, in which the molecular weight of (A) is below the lower limit, was inferior in moldability, and Comparative Example 5, in which the molecular weight exceeds the upper limit, was inferior in abrasion resistance, scratch resistance, and car wash scratch resistance, and neither of them was suitable for the present invention.
[0072] Next, the weather resistance was evaluated as follows.
[0073] Preparation of HC film 2 The photocurable resin compositions prepared in Examples 1 and 2 were added to the above Iupilon film, and a polycarbonate film (product name: PC-1151, manufactured by Teijin, thickness 200 μm), an acrylic film (product name: HBA007P, manufactured by Mitsubishi Chemical, thickness 125 μm), and a PET film (product name: U403, manufactured by Toray, thickness 125 μm) were used as substrates. The photocurable resin was applied to a dry film thickness of 3 μm, and the film was dried in a thermostatic chamber at 80°C for 1 minute, and then exposed to a high-pressure mercury lamp with an output of 1300 mW / cm. 2 The film was irradiated with ultraviolet light so that the accumulated light amount was 200 mJ to prepare HC film 2. This film was used only for evaluating weather resistance.
[0074] ΔE of the substrate alone and HC film 2: Using a color difference measuring device SD-6000 manufactured by Nippon Denshoku Industries Co., Ltd., the substrate alone not coated with the photocurable resin composition and the HC film 2 coated with the photocurable resin composition were measured in accordance with JIS Z 8722 using a UVB (0.55 W / m 2The color was measured before and after irradiation at 60°C for 1000 hours, and the difference ΔE was measured.
[0075] Weather resistance evaluation results Table 7 JPEG2024178663000007.jpg51135
[0076] It was confirmed that ΔE is greatly affected by the type of substrate, and that the selection of the substrate is important for improving weather resistance. It was also confirmed that the weather resistance of HC film 2 of Example 2, which contains the same composition as in Example 1 but with the addition of light stabilizer (E), is significantly improved.
[0077] Next, the injection molding was evaluated as follows.
[0078] Preparation of injection molded parts Using the HC film of Example 1, insert molding was actually performed using black ABS as the injection molding resin.
[0079] Appearance: Using a BYK painted surface quality measuring device, WaveScan 3 Dual, the film surface of the injection molded product and the painted surface of the painted steel plate were measured, and the LW (long wave) and SW (short wave) data were measured and compared.
[0080] Table 8 JPEG2024178663000008.jpg43145
[0081] The appearance of the insert molded product made by injection molding using the colored resin was free of the orange peel appearance defect that occurs with painted steel sheets.
Claims
1. A photocurable resin composition comprising: urethane acrylate (A) obtained by further reacting pentaerythritol triacrylate with a diisocyanate obtained by reacting ethylene glycol with isophorone diisocyanate; alumina fine particles (B); a leveling agent (C); and a photopolymerization initiator (D); wherein the weight average molecular weight of (A) is 2,000 to 12,000.
2. 2. The photocurable resin composition according to claim 1, further comprising a light stabilizer (E).
3. 3. A molding hard coat film comprising a plastic substrate and a cured layer of the photocurable resin composition according to claim 1 or 2 on the plastic substrate.
4. 4. The moldable hard coat film according to claim 3, wherein the moldable hard coat film is used for exterior applications of vehicles.
5. A method for producing an insert molded article, comprising the steps of: shaping the hard coat film for molding according to claim 3 using a mold; and then injecting a molten resin from the side opposite to the photocurable resin cured layer to form a resin molded article.
6. 4. An insert molded product or an out-molded product using the hard coat film for molding according to claim 3.
Citation Information
Patent Citations
Active energy ray-curable oligomer, active energy ray-curable resin composition, cured coating film, and plastic film
JP2011042770A
Curable composition, cured article and laminate
JP2016060839A
Hard coat coating composition and hard coat film for molding
JP2017178999A
Ultraviolet-curable resin composition and hard coat film
JP2018111793A
Photocurable resin composition and sheet
JP2019006897A
